DEVELOPMENT OF SPEED QUALITIES IN FUTSAL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the development of speed qualities in futsal students. Futsal, a fast-paced variant of football, requires agility, quick decision-making, and swift movements. The study examines different training methods, their impact on players, and subsequent results. The aim is to provide insight into optimizing the speed capabilities of futsal players to improve performance.